A new species of the Scinax catharinae species group (Anura: Hylidae) from the Atlantic rainforest of northeastern Minas Gerais, southeastern Brazil - Lourenco, Ana Carolina C. [UNESP]; Lacerda, Joao Victor A.; Goncalves Cruz, Carlos Alberto; Nascimento, Luciana Barreto; Pombal Jr, Jose P. (Magnolia Press, 2020)
We describe a new species of the Scinax catharinae group from one of the last remaining fragments of Atlantic Forest in northeastern Minas Gerais. The new species is distinguished from most species of the group mainly by having the mucronate snout in dorsal view, the unique light-yellow coloration on the gular surface in life contrasting with its overall color pattern, and the m. depressor mandibulae with an origin on the dorsal fascia at the level of the m. dorsalis scapulae. These two latter features are novelties in the diagnosis of Scinax species. The new species is currently known only from municipality of Santa Maria do Salto, state of Minas Gerais, Brazil. This locality is a remaining fragment of Atlantic Forest and has a peculiar geomorphic feature that has been poorly sampled so far.
Keywords: Taxonomy; morphology; myology; forest remnants